2015
DOI: 10.3892/or.2015.4427
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgetin exerts growth inhibitory and apoptotic effects on osteosarcoma cells through inhibition of STAT3 and activation of caspase-3/9

Abstract: Osteosarcoma is composed of tumor osteoblasts and bone-like tissues, with malignant tumors originating from osteogenesis organization. Osteosarcoma is a primary malignant bone tumor. Invasion and metastasis of osteosarcoma affect the prognosis of patients. However, effective therapeutic treatments remain to be identified. The aim of the present study was to investigate the possible inhibitory and apoptotic effects of ginkgetin in osteosarcoma cells. 3.3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Ginkgetin, derived from G. biloba leaves (<0.02% by dry weight) [ 49 ], has been shown to have anti-cancer activity in prostate cancer cells at micromolar concentrations [ 50 ]. In renal cell carcinoma and osteosarcoma, ginkgetin induced cell apoptosis through JAK2/STAT3 signaling [ 51 , 52 ]. We have screened several potential targets for ginkgetin, including Beclin1 and ATG7, and p62 is believed to be the most functional target ( Supplementary Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgetin, derived from G. biloba leaves (<0.02% by dry weight) [ 49 ], has been shown to have anti-cancer activity in prostate cancer cells at micromolar concentrations [ 50 ]. In renal cell carcinoma and osteosarcoma, ginkgetin induced cell apoptosis through JAK2/STAT3 signaling [ 51 , 52 ]. We have screened several potential targets for ginkgetin, including Beclin1 and ATG7, and p62 is believed to be the most functional target ( Supplementary Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, kaempferol, isorhamnetin, ginkgolide and bilobalide are the most studied constituents within Ginkgo Folium for cancer therapy. Indeed, ginkgetin, a bioflavonoid in Ginkgo Folium, has been shown to have anti-cancer activity in prostate cancer ( You et al, 2013 ), renal carcinoma ( Ren et al, 2016 ) and osteosarcoma ( Xiong et al, 2016 ). Moreover, the treatment of ginkgetin in lung cancer cells bearing mice could markedly reduce the tumor size, and which was proposed to be mediated by an autophagy-mediated cell death ( Lou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial-mediated apoptosis has two signaling pathways for programmed cell death: the death receptor pathway and the mitochondrial pathway, which are regulated via caspase-9 and caspase-8, respectively (23). Previous research has shown that caspases play significant roles in the apoptotic cascade (24,25). In the mitochondrial (intrinsic) pathway, members of the Bcl-2 family can regulate apoptosis downstream of caspase protein activation.…”
Section: Discussionmentioning
confidence: 99%